2016
DOI: 10.4292/wjgpt.v7.i3.361
|View full text |Cite
|
Sign up to set email alerts
|

Infertility in men with inflammatory bowel disease

Abstract: Inflammatory bowel disease (IBD) predominantly affects young adults. Fertility-related issues are therefore important in the management of patients with IBD. However, relatively modest attention has been paid to reproductive issues faced by men with IBD. To investigate the effects of IBD and its treatment on male fertility, we reviewed the current literature using a systematic search for published studies. A PubMed search were performed using the main search terms "IBD AND male infertility", "Crohn's disease A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
36
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(44 citation statements)
references
References 83 publications
1
36
0
3
Order By: Relevance
“…In agreement with results of the present study, Skondras et al 24 reported that cyclosporine enhances the inflammatory processes in the testis, possibly by increasing the expression of TGF‐β1, TNF‐α, IL‐6 and IL‐1β, which in turn leads to significant DNA damage which directly affects male fertility. Moreover, Shin and Okada 25 found that treatment of inflammatory bowel diseases with cyclosporine may affect NF‐κB signalling pathways which together with increased expression of TGF‐β1 may initiate massive release of the proinflammatory cytokines such as TNF‐α which is the main mediator of inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…In agreement with results of the present study, Skondras et al 24 reported that cyclosporine enhances the inflammatory processes in the testis, possibly by increasing the expression of TGF‐β1, TNF‐α, IL‐6 and IL‐1β, which in turn leads to significant DNA damage which directly affects male fertility. Moreover, Shin and Okada 25 found that treatment of inflammatory bowel diseases with cyclosporine may affect NF‐κB signalling pathways which together with increased expression of TGF‐β1 may initiate massive release of the proinflammatory cytokines such as TNF‐α which is the main mediator of inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, an IRA operation requires less pelvic dissection, which means lower risk of pelvic infection or adhesions and a future better fecundability and fertility, for both men and women, than in IPAA patients [24,[44][45][46].…”
Section: Association Between Macroscopic and Microscopic Grades Of Inmentioning
confidence: 99%
“…CED-erkrankte Männer sollten aktiv auf einen möglichen Kinderwunsch angesprochen werden, um (unbegründete?) Ängste zu erfahren und diesen eventuell argumentativ zu begegnen [17,18].…”
Section: Andere Medikamenteunclassified